Cerebellar continuous theta burst stimulation reduces levodopa-induced dyskinesias and decreases serum BDNF levels - Sanna, Angela; Follesa, Paolo; Puligheddu, Monica; Cannas, Antonino; Serra, Mariangela; Pisu, Maria Giuseppina; Dagostino, Sabino; Solla, Paolo; Tacconi, Paolo; Marrosu, Francesco (Neuroscience letters, 2020)
•A single session of cerebellar cTBS causes a reduction of LIDs in PD patients.•The reduction of LIDs is accompanied by a decrease in BDNF serum levels.•BDNF Val66Met polymorphism may influence the clinical and biological effect of cTBS. Patients with Parkinson’s Disease (PD) experience bothersome motor fluctuations and Levodopa-induced Dyskinesias (LIDs). Cerebellar continuous theta burst stimulation (cTBS) was used as an inhibitory protocol of repetitive transcranial magnetic stimulation (rTMS) to reduce LIDs in PD patients. The influence of Val66Met polymorphism of Brain Derived Neurotrophic Factor (BDNF) gene on the therapeutic response to cTBS was investigated and the serum levels of BDNF were measured before and after treatment. Eleven patients were exposed to a session of cTBS and sham stimulation (one week apart) after the administration of 125 % of their usual morning dose of Levodopa and LIDs were video-recorded and evaluated at different time points (0, 15, 30, 45, 60, 90 min after Levodopa). Cerebellar cTBS significantly reduced LIDs with respect to sham stimulation and decreased serum BDNF levels. These effects were evident in the Val66Val group (7 subjects) but not in the Val66Met group (4 subjects). These data confirm the efficacy of cerebellar cTBS in reducing LIDs in PD patients and show that the clinical effect is accompanied by a decrease in serum BDNF levels. Moreover, they suggest that BDNF Val66Met polymorphism may influence the clinical and biological response to cTBS.